Detailed investigations on thermal mode instabilities in LMA Yb-doped fibers - Beier, Franz; Sattler, B.; Liem, A.; Haarlammert, N.; Schreiber, Thomas; Eberhardt, Ramona; Tunnermann, Andreas (Optics InfoBase Conference Papers, 2017)
We present our investigations on modal instabilities using a commercial LMA fiber with 25 um core and 400 um cladding. The transversal mode instability (TMI) threshold is measured for different seed wavelengths and bending diameters in a systematic way. Additionally, in-situ temperature measurements up to the TMI threshold allowed measuring the longitudinal resolved thermal load and, thereby, fixing parameters for simulations that match experimental values. In conclusion, we derive driving parameters for TMI and found that photodarkening has a negligible impact on TMI in this fiber.
CRIS-Team Scopus Importer:2023-04-20